Concept of Punishment on Early Marriage, Islamic Perspective: کم عمری کی شادی پر سزا کا تصور اور اسلامی نقطہ نظر - Sarwar, Hira (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Early Marriage is acceptable in almost every religion in the world. In Islam the age of marriage is not set but varies according to the regions and natures of the humans. In some areas kids get puberty in early age whereas in other area kids get puberty in their 18s so we can not specify the age. Some circumstances occurred where early marriage become necessity of the time. In Pakistan there are the laws which have flaws in it. Child Marriage restraint act is one of them. Where early marriage is punishable for the groom and bride’s parents. While if the couple get married by their own will without the permission of the Wali or parents, they will be free to do anything. Here we will discuss laws about early marriages and their different situations. We will compare these laws and situations according to Islamic scenarios.